The pivotal role of TGF-β/Smad pathway in fibrosis pathogenesis and treatment - Chen, Feilong; Lyu, Lei; Xing, Chengyuan; Chen, Yu; Hu, Shaofan; Wang, Meng; Ai, Zhengdong (Frontiers in Oncology, 2025)
Fibrosis, which is characterized by pathological extracellular matrix (ECM) accumulation impairing organ function, is governed primarily by dysregulated transforming growth factor-β (TGF-β)/Smad signalling. TGF-β1 triggers canonical (Smad2/3-dependent) and noncanonical pathways upon receptor binding, driving profibrotic processes such as fibroblast activation, epithelial–mesenchymal transition (EMT), excessive ECM production (e.g., collagen), and the suppression of matrix degradation. This pathway is central to organ-specific fibrogenesis: In liver fibrosis, it activates hepatic stellate cells (HSCs); in renal fibrosis, it promotes tubular injury and ECM deposition; in pulmonary fibrosis, it induces EMT/fibroblast transition in radiation/bleomycin models; in cardiac fibrosis, it mediates fibroblast activation in diabetic cardiomyopathy/atrial fibrillation via NPRC/TGIF1/USP mechanisms; and in skin fibrosis (e.g., scleroderma), it stimulates collagen overproduction, which is suppressed by osthole or mesenchymal stem cells. The TGF-β/Smad axis thus represents a pivotal therapeutic target. Future research should clarify tissue-specific regulatory networks and develop combinatorial antifibrotic strategies.